The Effect of Henna Plant Extract (Lawsonia inermis L.) on Fibroblasts Formation in the Wound Healing Process After Tooth Extraction in Male Wistar White Rats (Rattus norvegicus) - Andriansyah; Nabilla Putri Amelya; Edrizal; Resa Ferdina (Jurnal Penelitian Pendidikan IPA, 2026)
Wound healing is a complex biological process consisting of inflammation, proliferation, and tissue remodeling phases. Complications following tooth extraction, such as infection and delayed healing, may interfere with this process. Lawsonia inermis L. (henna) leaves are widely used in traditional medicine and contain bioactive compounds with potential therapeutic effects. The main active compound, lawsone (2-hydroxy-1,4-naphthoquinone), along with flavonoids and tannins, exhibits antimicrobial, anti-inflammatory, and antioxidant properties that may stimulate fibroblast proliferation and support connective tissue regeneration. This study aimed to evaluate the effect of henna leaf extract on fibroblast formation during the wound healing process after tooth extraction in male Wistar rats (Rattus norvegicus). This laboratory experimental study used a posttest-only control group design involving 30 male Wistar rats divided into five groups: a negative control group, a positive control group, and three treatment groups receiving henna leaf extract at concentrations of 20%, 30%, and 40%. Histological observations of fibroblast cells were performed on days 3, 7, and 14 after tooth extraction. Statistical analysis using one-way ANOVA showed a highly significant difference among groups (Sig. = 0.000; p < 0.001). Further analysis with the LSD test indicated that the 40% henna extract group had significantly higher fibroblast counts compared with the control groups (p < 0.05). In conclusion, henna leaf extract significantly increases fibroblast formation in post-extraction wound healing, with the 40% concentration showing the most effective results. These findings suggest that henna leaf extract has potential as a natural therapeutic agent for promoting wound healing after tooth extraction and may contribute to the development of herbal-based dental treatment materials.